Analisis Metode dan Program Aftercare Penanganan Klien pada Panti Rehabilitasi LRPPN Bhayangkara Indonesia - Jihan Zhafira; Joy Syalom Margareth Sipahutar; Birgita Audrey Br Tarigan; Muhammad Hirzi Zhafari; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2023)
Narcotics abuse is a big challenge for the Indonesian nation. One effort that can be made is implementing a program to minimize this abuse. There are many programs that can be used to tackle cases of narcotics abuse, one of which is a rehabilitation program. The rehabilitation program is carried out to reduce and suppress drug abuse. As in LRPPN BI which tends to use groupwork intervention methods in its programs. LRPPN-BI also tends to implement Therapeutic Community (TC) in every program it carries out. The rehabilitation institution offers an Aftercare Program after the resident has terminated either the Social Worker or the Institution. The existence of an Aftercare Program can be an alternative answer to the high number of cases of narcotics use again by former clients who have completed the program, because it has a strengthening impact that gives the impression of supervision. The Aftercare program is appropriate for use by LRPPN-BI to prevent former clients from experiencing relapse. In this writing, the researchers used interview and observation techniques with the help of informants who work at the Institute, apart from that, this writing used a qualitative research approach. The research results show that the use of the groupwork method (Therapeutic community) and the Aftercare program has had a good impact on clients/residents.